Dana-Farber Cancer Institute/Mass General Brigham Fellowship Response to the COVID-19 Pandemic. Issue 9 (September 2021) - Stern, Robert M.; Michaelson, M. Dror; Mayer, Erica L.; Parnes, Aric D.; Fogerty, Annemarie E.; LaCasce, Ann S.; Nipp, Ryan D.
Abstract : The coronavirus disease (COVID)-19 pandemic has affected graduate medical education training programs, including hematology-oncology fellowship programs, both across the United States and abroad. Within the Dana-Farber Cancer Institute/Mass General Brigham hematology-oncology fellowship program, fellowship leadership had to quickly reorganize the program's clinical, educational, and research structure to minimize the risk of COVID-19 spread to our patients and staff, allow fellows to assist in the care of patients with COVID-19, maintain formal didactics despite physical distancing, and ensure the mental and physical well-being of fellows. Following the first wave of patients with COVID-19, we anonymously surveyed the Dana-Farber Cancer Institute/Mass General Brigham first-year fellows to explore their perceptions regarding what the program did well and what could have been improved in the COVID-19 response. In this article, we present the feedback from our fellows and the lessons we learned as a program from this feedback. To our knowledge, this represents the first effort in the hematology-oncology literature to directly assess a hematology-oncology program's overall response to COVID-19 through direct feedback from fellows.